A high-throughput sequencing ecotoxicology study of freshwater bacterial communities and their responses to tebuconazole. Issue 3 (8th December 2014) - Pascault, Noémie; Roux, Simon; Artigas, Joan; Pesce, Stéphane; Leloup, Julie; Tadonleke, Rémy D.; Debroas, Didier; Bouchez, Agnès; Humbert, Jean-François
Abstract: The pollution of lakes and rivers by pesticides is a growing problem worldwide. However, the impacts of these substances on microbial communities are still poorly understood, partly because next-generation sequencing (NGS) has rarely been used in an ecotoxicology context to study bacterial communities despite its interest for accessing rare taxa. Microcosm experiments were carried out to evaluate the effects of tebuconazole (TBZ) on the structure and composition of bacterial communities from two types of freshwater ecosystem (lakes and rivers) with differing histories of pollutant contamination (pristine vs. previously exposed sites). Pyrosequencing revealed that bacterial diversity was higher in the river than in the lakes and in previously exposed sites than in pristine sites. Lakes and river stations shared very few OTUs, and differences at the phylum level were identified between these ecosystems (i.e. the relative importance of Actinobacteria and Gammaproteobacteria ). Despite differences between these ecosystems and their contamination history, no significant effect of TBZ on bacterial community structure or composition was observed. Compared to functional parameters that displayed variable responses, we demonstrated that a combination of classical methods and NGS is necessary to investigate the ecotoxicological responses of microbial communities to pollutants. Abstract : The combination of classical methods and NGS approach is necessary when tackling the ecotoxicological responses of microbial communities to pollutants. Abstract :